2021
DOI: 10.2147/cmar.s299066
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Characteristics and Prognosis of Breast Cancer in Young Women – A Single Center Study in a Developing Country

Abstract: Objective Breast cancer (BC) in young women tends to be more aggressive. This study highlights the clinicopathological features and outcomes of young breast cancer (YBC) patients in a developing country. Methods Consecutive patients aged 35 years or younger with a pathologically confirmed diagnosis of breast cancer treated and followed up at our department were included. Medical records and follow-up databases were reviewed and documented. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…We found that the black race had a higher risk of cumulative incidence and a poor prognosis, keeping in with previous studies 14,15 . Consistent with previous studies, BCYW has a predisposition to have high-grade tumors, visceral metastases, negative estrogen receptors, and positive HER2 status [19][20][21] . Kaplan-Meier curves suggest that patients under 40 years have longer OS and BCSS than older patients.…”
Section: Discussionsupporting
confidence: 90%
“…We found that the black race had a higher risk of cumulative incidence and a poor prognosis, keeping in with previous studies 14,15 . Consistent with previous studies, BCYW has a predisposition to have high-grade tumors, visceral metastases, negative estrogen receptors, and positive HER2 status [19][20][21] . Kaplan-Meier curves suggest that patients under 40 years have longer OS and BCSS than older patients.…”
Section: Discussionsupporting
confidence: 90%
“…Although luminal-A disease is associated with better prognosis, biological subtyping showed no difference between age groups, similar to the literature ( 6 , 21 , 23 ). Thus, differences in survival between age groups could not be related to only the biological subtype distribution.…”
Section: Discussionsupporting
confidence: 89%
“…The hormonal and Her-2 status in group Y was similar to that reported by Cancello et al ( 19 ). Sun et al ( 23 ) showed a significantly higher hormone negativity in young patients than in other developing countries.…”
Section: Discussionmentioning
confidence: 94%
“…Compared with elderly women, young patients, accounting for a relatively small number of breast cancer, were more likely to present aggressive subtypes and advanced disease, and the survival and outcomes were worse (5-year relative survival rate comparison: 86% vs 91% in elderly women) ( 5 ). Consequently, the strategies of treatment and prevention for young breast cancer have gradually aroused wide attention ( 7 11 ). Notably, in one study from China, young patients with breast cancer were more likely to have larger tumor size, poorer differentiation grade, a higher proportion of triple-negative breast cancer (TNBC), and more advanced stage, when compared with elder patients ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the strategies of treatment and prevention for young breast cancer have gradually aroused wide attention ( 7 11 ). Notably, in one study from China, young patients with breast cancer were more likely to have larger tumor size, poorer differentiation grade, a higher proportion of triple-negative breast cancer (TNBC), and more advanced stage, when compared with elder patients ( 11 ).…”
Section: Introductionmentioning
confidence: 99%